Multidimensionality in Impulsivity and Alcohol Use: A Meta‐Analysis Using the UPPS Model of Impulsivity. (11th April 2013) - Coskunpinar, Ayca; Dir, Allyson L.; Cyders, Melissa A.
Abstract : Background: Although there is considerable support for the relationship between impulsivity and alcohol use, the use of multidimensional conceptualizations of impulsivity and alcohol use has lead to varying relationship sizes across studies. The aims of the current meta‐analysis are to (i) examine variability in the magnitude of the bivariate relationship between impulsivity and alcohol use across studies and (ii) describe the pattern of effects between specific impulsivity traits and alcohol use variables, using the UPPS model of impulsivity. Methods: Ninety‐six studies were meta‐analyzed using a random effects model to examine the relationship between general impulsivity and alcohol use, as well as the relationships among separate impulsivity traits based in the UPPS model of impulsivity and specific alcohol use outcomes. Results: Results indicate that, in general, impulsivity and alcohol use are related ( r  =   0.28); however, this effect size varied significantly across studies (from −0.05 to 1.02). Drinking quantity was most strongly predicted by lack of perseverance ( r  =   0.32), whereas all traits equally predicted drinking frequency. Drinking problems were most highly related to negative ( r  =   0.35) and positive ( r  =   0.34) urgency, and alcohol dependence was most highly related to negative urgency ( r  =   0.38) and lack of planning ( r  =   0.37). Conclusions: Effect sizes between impulsivity and alcohol use vary significantly by UPPS trait used in each study; thus, findings suggest and further reinforce the view in the literature that specific impulsivity‐related constructs differentially relate to specific alcohol use outcomes.